Game-Based Learning: Academic Games sebagai Metode Penunjang Pembelajaran Kewirausahaan - Rahmat Hidayat (Faculty of Psychology Universitas Gadjah Mada, 2018)
Entrepreneurship plays an important role in national economic growth. Therefore, the character development, the way of thinking, and entrepreneurial skills within the community are things that should be sought. Consequently, the effective entrepreneurship learning methods are needed, specifically kind of method based on adult learning approach. This article seeks to bring the study of digital games technology as an entrepreneurial learning media. Hence, the description of the characteristics of games and learning aspects that can be facilitated by digital games technology will be mainly discussed. In addition, this article describes the learning process through digital media, instructional techniques that can be integrated into digital media, and assessment feedback method in academic games learning. Some examples of digital games used for learning in entrepreneurship courses are presented to provide a concrete picture. In brief, this article supports the use of digital games technology in entrepreneurial learning.